ASSESSMENT OF OPTIMALITY LEVEL OF ACCUMULATED STRAIN DISTRIBUTION IN FORGINGS MADE IN OPEN PRESS TOOLS - Armenak V. Vovchenko (Advanced Engineering Research, 2011)
The generalized estimation technique of the optimality level of the strain distribution in the forgings is offered. The technique is based on the estimated results of the pressing optimization reduced to the consistent criterion. Function parameters of the boundary frames of the numerical and physical pressing simulation are defined. They classify the design solutions by the analogous to the optimal, rational and nonrational ones depending on the factor of the geometrical complication of the final shape.